Diverticulitis: A Review of Current and Emerging Practice-Changing Evidence - Wu, Sonia; Al Khaldi, Maher; Richard, Carole S.; Dagbert, François (Clinics in Colon and Rectal Surgery, 2023)
Acute diverticulitis represents a common colorectal emergency seen in the Western world. Over time, management of this condition has evolved. This review aims to highlight recent evidence and update current recommendations. Notable evidence has emerged in certain aspects of diverticulitis. This includes disease pathogenesis, as emerging data suggest a potentially greater role for the microbiome and genetic predisposition than previously thought. Acute management has also seen major shifts, where traditional antibiotic treatment may no longer be necessary for acute uncomplicated diverticulitis. Following successful medical management of acute diverticulitis, indications for elective sigmoidectomy have decreased. The benefit of emergency surgery remains for peritonitis, sepsis, obstruction, and acute diverticulitis in certain immunocompromised patients. Routine colonoscopy, once recommended after all acute diverticulitis episodes, has been shown to be beneficial for cancer exclusion in a distinct patient population. Despite advances in research, certain entities remain poorly understood, such as smoldering diverticulitis and symptomatic uncomplicated diverticular disease. As research in the field expands, paradigm shifts will shape our understanding of diverticulitis, influencing how clinicians approach management and educate patients.
Keywords: diverticulitis; diverticular disease; acute care surgery; colorectal surgery